2010
DOI: 10.1068/b35078
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evolution of Urban Form and Land-Use Structure in Hangzhou, China: Evidence from Fractals

Abstract: Using fractal theory and urban land-use maps for 1949, 1959, 1980, and 1996, this study is devoted to analyzing the evolutionary features of urban form and land-use structure in Hangzhou, China. We find that self-similarity exists in both the built-up area and the municipal area, and fractal properties tend to become better defined with time. The fractal dimension of each type of land use is less than that of all land use. From 1980 to 1996, the fractal dimensions of residential, industrial, and external trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 25 publications
3
91
0
4
Order By: Relevance
“…Therefore, measurement of land urbanization is as important as population urbanization. The dynamic evaluation of land urbanization focuses mainly on measuring the quantity, speed and change of land-use structures Wang and Li, 2011;Deng et al, 2009;Xu et al, 2009;Tang, 2009;Feng and Chen, 2010;Zhang et al, 2010;Dong et al, 2011). However, most of the research is based on single or limited cases, which are unfavorable for inter-city comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, measurement of land urbanization is as important as population urbanization. The dynamic evaluation of land urbanization focuses mainly on measuring the quantity, speed and change of land-use structures Wang and Li, 2011;Deng et al, 2009;Xu et al, 2009;Tang, 2009;Feng and Chen, 2010;Zhang et al, 2010;Dong et al, 2011). However, most of the research is based on single or limited cases, which are unfavorable for inter-city comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of box counting can be applied to fractal dimension estimation of cities [31,42]: one is to fix the largest box [46], and the other is to unfix the largest box [44]. In the former way, the size and shape of the first level box do no change for different years; in the latter way, the size and shape of the largest box change with urban growth in different years.…”
Section: Results and Findings Based On Fixed Box Methodsmentioning
confidence: 99%
“…The spatial patterns of Hangzhou's urban land use bear fractal structure, and can be characterized with fractal dimension (Figure 6). Using the functional box-counting method, Feng and Chen [44] once calculated the capacity dimension of Hangzhou's urban form in four different years (1949, 1959, 1980, and 1996). Different from the case of Beijing city, the variable boxes were employed to make spatial measurement for suiting city sizes in different years.…”
Section: Observational Evidences and Findings Based On Unfixed Box Mementioning
confidence: 99%
See 1 more Smart Citation
“…The relations between the fractal dimension of urban form and landscape patterns were discussed based on fractal theory and urban land-use maps [51,52].Terzi and Kaya [53] found that the fractal dimension of urban areas presented a positive correlation with the urban sprawl index. In this research, it indicated that some landscape metrics showed positive correlations with the fractal dimension (LSI, TE), and some showed negative correlations (ED, CI).…”
Section: Factors Associated With Built-up Land Expansion Patternsmentioning
confidence: 99%